HUBUNGAN KARAKTERISTIK INDIVIDU, BUDAYA ORGANISASI, DAN ORGANIZATION CITIZENSHIP BEHAVIOR DENGAN KINERJA ORGANISASI - Arie Ambarwati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
Organizational performance / company been an research will is always interesting to talk about in the business world or the management of organization. Several factors and variables affecting the performance of the organization. This study attempts to analyze the individual characteristics, relationship the culture of the organization citizenship behavior (OCB) with performance / organization company. Quantitative research methodology used is explanatory using 35 respondents an employee in the services sector financial Surabaya city consultation. The research suggests that there is a directly or indirectly between individual characteristics, cultural organization, organization citizenship behavior (OCB) with organizational performance. The analysis showed that only cultural organizations and organization citizenship behavior (OCB) giving immediate and significant relationship with, organizational performance while individual characteristics not giving the correlations directly with. organizational performance.